2018
DOI: 10.1103/physrevd.97.083012
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of the break in DAMPE lepton spectra

Abstract: Recently, DAMPE has released its first results on the high-energy cosmic-ray electrons and positrons (CREs) from about 25 GeV to 4.6 TeV, which directly detect a break at ∼ 1 TeV. This result gives us an excellent opportunity to study the source of the CREs excess. In this work, we used the data for proton and helium flux (from AMS-02 and CREAM),p/p ratio (from AMS-02), positron flux (from AMS-02) and CREs flux (from DAMPE without the peak signal point at ∼ 1.4 TeV) to do global fitting simultaneously, which c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 150 publications
(206 reference statements)
0
20
1
Order By: Relevance
“…In such a case the DC2 model actually returns to the plain diffusion model. The parameter v A in the DR2 model is fitted to be about 29.4 km s −1 , which is smaller than that inferred in the traditional diffusion reacceleration model configuration (i.e., η = 1; hereafter DR) [4,5,10,11]. This is due to the β η term in the diffusion coefficient compensates to some degree the reacceleration effect required to reproduce the bump of the B/C ratio (see below).…”
Section: A Propagation Parametersmentioning
confidence: 82%
See 2 more Smart Citations
“…In such a case the DC2 model actually returns to the plain diffusion model. The parameter v A in the DR2 model is fitted to be about 29.4 km s −1 , which is smaller than that inferred in the traditional diffusion reacceleration model configuration (i.e., η = 1; hereafter DR) [4,5,10,11]. This is due to the β η term in the diffusion coefficient compensates to some degree the reacceleration effect required to reproduce the bump of the B/C ratio (see below).…”
Section: A Propagation Parametersmentioning
confidence: 82%
“…[10] gives z h = 5.0 ± 0.9 kpc, which is consistent with this work. The fits with the DR model configuration using different data sets gave 5.4 ± 1.4 kpc [4], 3.3±0.6 [5], 5.9±1.1 [10], and 7.4±0.6 [11]. The value of δ is found to be about 0.5 (0.4) for the DC2 (DR2) model at high rigidities.…”
Section: A Propagation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such an excess may originate from certain new unobserved astrophysical sources, it may also be explained by DM annihilation [3]. Relevant discussion on this subject can be found in [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and one notable conclusion is that if one assumes the e + e − cosmic-ray spectrum to be generated directly from DM annihilation in a nearby clump halo, the best fit values for the DM particle mass, the DM clump mass and the annihilation luminosity are around 1.5 TeV, 10 6−8 M and 10 64−66 GeV 2 cm −3 , respectively, if the subhalo is about 0.1 ∼ 0.3 kpc away from the earth [3].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed modeling of the GCR acceleration and propagation is difficult, due to the tanglement of the above mentioned effects and in general only the data around the Earth are available. The traditional way is to model each of those effects, and fit globally to the data (Putze et al 2009(Putze et al , 2010Trotta et al 2011;Jin et al 2015;Jóhannesson et al 2016;Korsmeier & Cuoco 2016;Feng et al 2016;Yuan et al 2017;Niu & Li 2018). It is found that there is large degeneracy among different models and the corresponding parameters (Yuan et al 2017;Niu & Li 2018).…”
Section: Introductionmentioning
confidence: 99%